(untitled) (Iranian Journal of Kidney Diseases, 2019)
Introduction. The mortality rate in patients with acute kidney injury (AKI) is high. The aim of this study was to evaluate the efficacy of treatment with adipose-derived mesenchymal stem cells (AD-MSC) in renal ischemia-reperfusion (I/R) model in rats. Methods. In this study 28 male Wistar rats were divided into four groups of control, sham, I/R24h+PBS, and I/R24h+AD-MSC. Blocking the renal arteries for 45 minutes induced renal I/R and then reperfusion was conducted for 24 hours. Parameters including urine volume, osmolarity, plasma creatinine (Crp), and blood urea nitrogen (BUN) were evaluated and values of creatinine clearance (CCr), absolute sodium excretion (UNaV°), fractional excretion of sodium (FENa), absolute potassium excretion (UKV°) and fractional excretion of potassium (FEK) were calculated. The right kidney was removed to measure the malondialdehyde (MDA) and ferric reducing antioxidant power (FRAP), as well as the left kidney for histological evaluation. Results. I/R caused a significant increase in Crp, BUN, UNaV°, FENa, FEK, MDA, and tissue damages. In addition, the values of CCr, urine osmolarity, and FRAP level decreased significantly (P < .05). Following AD-MSC treatment, values of FENa, Crp, FEK, MDA, and tissue damages decreased significantly, while urine osmolarity increased significantly in the I/R24h + AD-MSC group compared to the I/R24h + PBS group. Furthermore, FRAP values increased significantly (P < .001). Conclusion. Treatment with AD-MSC reduced tissue damage and oxidative stress while increasing antioxidant activity. In addition, it improved kidney function after 45 min ischemia and 24 h reperfusion.